2020
DOI: 10.3390/genes11010051
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Next-Generation Sequencing in Patients with Suggestive X-Linked Intellectual Disability

Abstract: X-linked intellectual disability (XLID) is known to contribute up to 10% of intellectual disability (ID) in males and could explain the increased ratio of affected males observed in patients with ID. Over the past decade, next-generation sequencing has clearly stimulated the gene discovery process and has become part of the diagnostic procedure. We have performed targeted next-generation sequencing of 82 XLID genes on 61 non-related male patients with suggestive non-syndromic XLID. These patients were initiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 70 publications
0
22
0
3
Order By: Relevance
“…In families suspected of X-linked inheritance of ID, nextgeneration gene sequencing has proven useful for identifying a genetic etiology for ID (Ibarluzea et al 2020). SLC6A8 and SLC9A6 gene mutations are two such examples in the SLC superfamily.…”
Section: Intellectual Disability/autistic Spectrum Disordermentioning
confidence: 99%
“…In families suspected of X-linked inheritance of ID, nextgeneration gene sequencing has proven useful for identifying a genetic etiology for ID (Ibarluzea et al 2020). SLC6A8 and SLC9A6 gene mutations are two such examples in the SLC superfamily.…”
Section: Intellectual Disability/autistic Spectrum Disordermentioning
confidence: 99%
“…Since Garcia CC et al rstly connected SYN1 mutation with neurodevelopmental disorder in 2004, 16 causative variants including ten missense mutations, ve nonsense mutations, and one splicing site mutation in the gene have been identi ed (containing this study) (Fig. 2) [1,2,[7][8][9][10][11][12][13][14][15][16]. These variants are clustered in B linker domain (A51G, S79W), actin-binding and synaptic-vesicle binding C-domain (W126X, W126R, c.527+1G>A, S212I, G240R, V266M, W356X, T359K, R420G) and proline-rich D-domain (R422X, Q482X, A550T, Q555X, T567A) of the encoded protein as indicated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the clinical characteristics of SYN1-related disorder, we conducted a literature review of all reported pedigrees from the Pubmed and Embase on English articles. Clinical information of 7 pedigrees with the disorder from 7 studies was collected in the report (Table 1) [2,[9][10][11][12][13][14], and other cases were excluded for lack of detail descriptions [1,7,8,15,16]. Overall, we noticed that females are less susceptible than males due to X-chromosome random inactivation (XCI), however, few female carriers presented with mild intellectual disability and febrile seizures [8,14].…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing is available in the laboratory but has rarely been used in the clinic. Still, RNA sequencing has helped in re-evaluating and further classifying the genetic variants found by exome sequencing, such as confirmation of putative splicing mutations [205]. It is also used to determine whether 2 variants in the same gene are localized on the same or different chromosome and to detect monogenic defects undetected by exome sequencing (e.g., a deep intronic variant leading to a pseudoexon) [206, 207].…”
Section: Hypothetical Causes Of Short Stature Associated With a Low Serum Igf-i And Normal Stimulated Gh Peakmentioning
confidence: 99%